Monitoring The Learning Process at SMK Kesatrian Through Kana Buso Application - Pratama Puja Kusuma, Tyas; Prasetyo, Muhamad Awiet Wiedanto (Universitas Nusantara PGRI Kediri, 2020)
The research aims to produce applications that can analyze the quality of the questions, know the statistics of student grades, and determine the appropriateness of the items to be tested for the subjects of network system administration competence in Computer Network Engineering Class XI Vocational School Kesatrian. Research and development. The development model in this study uses the Analysis-Design-Development-Implementation-Evaluation (ADDIE) Model. With the stages of development, ranging from analysis, planning, development, implementation, and evaluation. The application is developed based on the website. This research resulted in the form of question items named Kana Buso Application, which is suitable as a medium for determining the quality of questions. This application is useful to make it easier for teachers to assess the quality of the items that will be given to students. Based on the test results, it can be concluded that the use of this application can also minimize student cheating in working on exam questions because the questions issued are random.